Cigarette smoking and radiographic progression in rheumatoid arthritis. Issue 8 (19th January 2007) - Finckh, A; Dehler, S; Costenbader, K H; Gabay, C
Abstract : Background: Smoking is a well-established environmental risk factor for the development of rheumatoid arthritis (RA). However, it remains unclear whether smoking influences RA disease progression and whether smokers have more radiographic damage progression than non-smokers over time. Objective: To compare the rates of radiographic damage progression in current smokers and non-smokers in a large prospective RA cohort. Methods: The SCQM-RA is a population-based registry monitoring disease activity, radiographic damage and symptoms at regular intervals. All patients in the SCQM-RA database with sequential plain radiographs were included. Joint erosions were assessed in 38 hand and foot joints with a validated scoring method. The rate of erosion progression was analysed using multivariate longitudinal regression models and adjusted for potential confounders. Results: 2004 RA patients with a mean of 3.6 sequential radiographs and 3.1 years of follow-up were included. The 545 (27%) current smokers smoked on average 16 cigarettes per day and had a mean past smoking exposure of 20.6 pack-years. Radiographic joint damage progressed at a similar rate in current smokers and non-smokers ( p =  0.26). However, smoking intensity was associated with a significant inverse dose–response; heavy smokers (>1 pack-day) progressed significantly less than non-smokers or moderate smokers (p<0.001). Conclusion: Radiographic joint damage progressed at an equivalent rate in smokers and non-smokers. Furthermore, a significant trend was observed for reduced radiographic progression and generally more favourable functional scores among heavy smokers, suggesting that cigarette smoke does not accelerate RA disease progression.